Solidarity economy in Colombia: authors and conceptual analysis (2020)
This publication is the result of the second of a three-phase analysis of the research on the conceptualization of solidarity economy in Colombia. The research was conducted by Red Unicossol, professors and researchers eager to make a contribution to the reflection and the dialogue that brings us closer to the identification of the epistemology of said concept. It also proposes the analysis of the documentation of three groups of interest, universities, entities of aggregation and integration of the solidary sector in Colombia, and networks and state entities, considering that these agents represent the voices of the sector, which will gain visibility through their publications. Initially, the publication presents a theoretical analysis of approximation to the approaches that can determine the concept; after that, it shows a qualitative and quantitative research methodological approach; finally, it reports the results of each focus group in three chapters. The approaches give us meeting points between the dialogue of these agents based on the concept of solidarity economy in Colombia, characteristics that bring us closer to common ends. Nevertheless, the first conclusion is the recognition of the plurality of expressions in society, which invites us to maintain permanent dialogue for the recognition of others, with those who co-construct social and solidarity realities in the framework of a different way of influencing economy.